PERSEPSI MASYARAKAT DESA CIHANJUANG TENTANG DONOR DARAH: STUDI KUALITATIF - Malinti, Evelin; Elon, Yunus (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021, 2021)
Donating blood is a noble act that can save lives. The study aimed to assess the perception of the community in Cihanjuang Village about blood donation. The study utilized a qualitative method, where informants were the main source of information. A total of 7 informants who were selected using the nonprobability sampling method. The data was collected by interviewing and recording the statements of the informants, then verbatim transcripts were made and analyzed to determine the cognator. Results: As many as 71% of informants have never donated blood, 29% have donated blood. What informants know about blood donation is donating blood, forming new blood, and helping others. Informants are willing to donate blood to strangers and if someone is in need. Feelings Informants are sincere, volunteer and help others, are satisfied and happy. For the informants, blood donation would be healthy and not harmful and said that people who are menstruating cannot donate blood. Conclusion: Although the majority of informants have never donated blood, the informants have a positive view and are willing to donate blood for those in need